Negative feedback buffers effects of regulatory variants - Bader, Daniel M.; Wilkening, Stefan; Lin, Gen; Tekkedil, Manu M.; Dietrich, Kim; Steinmetz, Lars M.; Gagneur, Julien (Molecular Systems Biology, 2015)
Mechanisms conferring robustness against regulatory variants have been controversial. Previous studies suggested widespread buffering of RNA misexpression on protein levels during translation. We do not find evidence that translational buffering is common. Instead, we find extensive buffering at the level of RNA expression, exerted through negative feedback regulation acting in trans, which reduces the effect of regulatory variants on gene expression. Our approach is based on a novel experimental design in which allelic differential expression in a yeast hybrid strain is compared to allelic differential expression in a pool of its spores. Allelic differential expression in the hybrid is due to cis-regulatory differences only. Instead, in the pool of spores allelic differential expression is not only due to cis-regulatory differences but also due to local trans effects that include negative feedback. We found that buffering through such local trans regulation is widespread, typically compensating for about 15% of cis-regulatory effects on individual genes. Negative feedback is stronger not only for essential genes, indicating its functional relevance, but also for genes with low to middle levels of expression, for which tight regulation matters most. We suggest that negative feedback is one mechanism of Waddington's canalization, facilitating the accumulation of genetic variants that might give selective advantage in different environments. Synopsis Local trans regulation, mainly due to negative feedback, buffers effects of cis-regulatory variants by about 15%. This buffering is stronger for essential genes and genes with low to middle expression levels, for which tight regulation matters most. Novel experimental design using expression of a diploid hybrid and its haploid spores allows systematic dissection of cis and local trans regulation. Local trans effects buffer effects of cis-regulatory variants in yeast by typically 15%. Local trans buffering is primarily due to negative feedback. Negative feedback as robustness strategy for genes with low to medium expression level. Local trans regulation, mainly due to negative feedback, buffers effects of cis-regulatory variants by about 15%. This buffering is stronger for essential genes and genes with low to middle expression levels, for which tight regulation matters most.
CRIS-Team Scopus Importer:2023-03-11
Keywords: buffering; canalization; cis regulation; feedback; trans regulation